PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK AKHLAKUL KARIMAH SISWA PADA MASA PANDEMI COVID-19 - Elin Nakmah; Fauzi Al Mubarok (STIT Islamic Village Tangerang, 2022)
This research aims to obtain data on the role of Islamic religious education teachers in shaping students' morality during the Covid-19 pandemic at SMK Al-Hikmah Curug Tangerang and to find out the obstacles faced by the role of Islamic religious education teachers in shaping students' morality during the Covid-19 pandemic. 19 at SMK Al-Hikmah Curug Tangerang. This study uses qualitative research to obtain the required research data. Data collection techniques using the method of observation, interviews and documentation. The technique of testing the validity of the data is through Credibility, Transferability, Dependability, Confirmability. Data analysis techniques through data collection, data reduction, data presentation and verification. The results of this study indicate that the role of Islamic religious education teachers in shaping the morality of students during the Covid-19 pandemic at SMK Al-Hikmah Curug Tangerang is using online learning. The type of education used is formal and informal. The learning process of Islamic religious education teachers relates the material to the character values and daily worship of students. The media used are Zoom, Google From, Class Room and Whatsapp applications. In giving advice the teacher uses flyers that the teacher distributes to students, quotes from the Qur'an and hadith. While the obstacles in conducting the assessment are internet connections, lack of control over student behavior while at home, students' laziness in doing assignments and collecting assignments not on time, delivering material to different students' admissions.